2020
DOI: 10.1017/s0954422420000116
|View full text |Cite
|
Sign up to set email alerts
|

Oral and nasal probiotic administration for the prevention and alleviation of allergic diseases, asthma and chronic obstructive pulmonary disease

Abstract: Interaction between a healthy microbiome and the immune system leads to body homeostasis, as dysbiosis in microbiome content and loss of diversity may result in disease development. Due to the ability of probiotics to help and modify microbiome constitution, probiotics are now widely used for the prevention and treatment of different gastrointestinal, inflammatory, and, more recently, respiratory diseases. In this regard, chronic respiratory diseases including chronic obstructive pulmonary disease (COPD), asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 115 publications
(190 reference statements)
0
27
0
Order By: Relevance
“…It has been reported that probiotic with regulating the balance of intestinal microecology exerts prophylactic and alleviating effects on diseases, such as allergic asthma [ 20 , 21 ], atopic dermatitis [ 22 , 23 ], and influenza infection [ 24 , 25 ], but the correlation between clinical characters of influenza infection and gut microbial alteration needs to be explained. Based on the gut–lung axis theory, the bi-directional cross-talk between lung and gut intricately influences the homeostasis of both [ 26 ], and therefore, the deeper understanding of gut microbial alteration on alleviating respiratory disorders contributes to therapeutic applications using probiotic strains.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that probiotic with regulating the balance of intestinal microecology exerts prophylactic and alleviating effects on diseases, such as allergic asthma [ 20 , 21 ], atopic dermatitis [ 22 , 23 ], and influenza infection [ 24 , 25 ], but the correlation between clinical characters of influenza infection and gut microbial alteration needs to be explained. Based on the gut–lung axis theory, the bi-directional cross-talk between lung and gut intricately influences the homeostasis of both [ 26 ], and therefore, the deeper understanding of gut microbial alteration on alleviating respiratory disorders contributes to therapeutic applications using probiotic strains.…”
Section: Discussionmentioning
confidence: 99%
“…The modern Paleolithic diet (PD) is a different approach characterized by a high intake of vegetables, fruits, nuts, eggs, fish and meat, minimizing that of grains, cereals, legumes, dairy products, and processed foods [ 14 ]. Recently, it has sparked increasing interest due to its alleged beneficial effects on the prevention and treatment of diabetes, cancer, and cardiovascular diseases [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Airway mucosal immunity has some potential benefits such as painlessness, simplicity, low dose, good tolerance, and safety [ 28 ]. Many studies have indicated that nasal probiotic administration can efficiently regulate the immune response in several chronic respiratory diseases, including allergic rhinitis, asthma, and chronic pulmonary obstructive disease, sometimes more effective than the oral route [ 6 , 29 ]. However, there are questions about the safety of nasal probiotics administration, as it can easily cause lung infection or bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that exposure to an environment rich in beneficial microorganisms can reduce the risk of asthma [ 4 , 5 ]. These protective microorganisms may regulate the immune system through the respiratory tract or intestine, providing protection against asthma [ 4 , 6 ]. Probiotics are a set of living nonpathogenic microorganisms that confer beneficial effects on the health of the host when administered in adequate quantities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation